2010
DOI: 10.1111/j.1758-0854.2010.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Gender, and Emotional Labor Strategies on Job Outcomes: Moderated Mediation Analyses

Abstract: Based on socioemotional selectivity theory (SST; Carstensen, Isaacowitz, & Charles, 1999), we examined the role of age on the selection of emotional labor strategies, and how the latter mediated the association between age / gender and job satisfaction as well as psychological health. We also examined whether gender would moderate the association between age and emotional labor strategies. Correlation results showed that age was related to the use of deep acting and the expression of naturally felt emotions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 44 publications
5
74
1
8
Order By: Relevance
“…Age was selected as a variable based on the studies by Schaubroeck and Jones (2000) and Cheung and Tang (2010). According to Carstensen's socioemotional selectivity theory (Carstensen, Isaacowitz, & Charles, 1999), older individuals, because of years of work experience, are more cognizant than younger individuals regarding what kinds of work events influence emotions positively and negatively (Cho, Rutherford, & Park, 2013).…”
Section: Controlled Linkagesmentioning
confidence: 99%
“…Age was selected as a variable based on the studies by Schaubroeck and Jones (2000) and Cheung and Tang (2010). According to Carstensen's socioemotional selectivity theory (Carstensen, Isaacowitz, & Charles, 1999), older individuals, because of years of work experience, are more cognizant than younger individuals regarding what kinds of work events influence emotions positively and negatively (Cho, Rutherford, & Park, 2013).…”
Section: Controlled Linkagesmentioning
confidence: 99%
“…H2: Personality is positively associated to emotional labor. Association between Emotional Labor and Burnout Grandey et al (2012) revealed that deep acting is positively associated to increased job satisfaction [30], and increased personal accomplishment (Cheung & Tang, 2010) [31]. Surface acting is positively related with emotional exhaustion exhaustion in teachers but they didn't find any positive association between deep acting and burnout.…”
Section: The Job Demand Resource Theory (Jd-r)mentioning
confidence: 99%
“…Zależności między strategiami pracy emocjonalnej a dobrostanem pracownika często są wyjaśniane [16,17] na gruncie teorii zachowania zasobów (conservation of resources -COR) Hobfolla [18]. Zgodnie z nią źródłem stresu jest rzeczywista utrata zasobów lub ryzyko utraty.…”
unclassified
“…Z kolei okazywanie emocji naturalnie odczuwanych nie wymaga wydatkowania energii i zasobów, może natomiast prowadzić do pozyskania zasobów, ponieważ wiąże się z większą satysfakcją i mniejszym dystresem w pracy, a także z poczuciem osiągnięć osobistych [19,17].…”
unclassified
See 1 more Smart Citation